A self-regulatory cell-wall-sensing module at cell edges controls plant growth - Elliott, Liam; Kalde, Monika; Schürholz, Anne-Kathrin; Zhang, Xinyu; Wolf, Sebastian; Moore, Ian; Kirchhelle, Charlotte (Nature plants, 2024)
Morphogenesis of multicellular organs requires coordination of cellular growth. In plants, cell growth is determined by turgor pressure and the mechanical properties of the cell wall, which also glues cells together. Because plants have to integrate tissue-scale mechanical stresses arising through growth in a fixed tissue topology, they need to monitor cell wall mechanical status and adapt growth accordingly. Molecular factors have been identified, but whether cell geometry contributes to wall sensing is unknown. Here we propose that plant cell edges act as cell-wall-sensing domains during growth. We describe two Receptor-Like Proteins, RLP4 and RLP4-L1, which occupy a unique polarity domain at cell edges established through a targeted secretory transport pathway. We show that RLP4s associate with the cell wall at edges via their extracellular domain, respond to changes in cell wall mechanics and contribute to directional growth control in Arabidopsis.
Gesehen am 29.07.2024